은 나노 연고가 측두하악관절낭염의 환자의 치료에 미치는 영향에 관한 연구 - 채창훈(Chang-Hoon Chae); 김좌영(Jwa-Young Kim); 김미자(Mi-Ja Kim); 정훈(Hoon Chung); 김승호(Seung-Ho Kim); 오현우(Hyun-Woo Oh); 김영남(Young-Nam Kim); 김영일(Young-Il Kim); 양병호(Byung-Ho Yang); 김성곤(Seong-Gon Kim) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2006)
The silver nanocrystalline is widely used for biological field because of its biocompatibility and anti-microbial effect. The objective of this study was to evaluate the therapeutic efficacy of the silver nanocrystalline ointment on the temporomandibular joint (TMJ) capsulitis. Total 39 patients were included in this study and all patients were received single topical application of the silver nanocrystalline ointment (group A, n=30) or placebo ointment (group B, n=19). Measured variables were maximum mouth opening (MMO), visual analog scale (VAS) for pain, and VAS for function. In results, we could not assess any therapeutic efficacy of single application in the chronic TMJ capsulitis (p>0.05). However, the single application of silver nanocrystalline ointment showed significant improvement in MMO and VAS for pain compared to placebo effect in the acute TMJ capsulitis (p<0.05). We could not find any complications related to ointment application in both groups. In conclusion, the single application of silver nanocrystalline ointment was effective in improving patient’s symptom in acute TMJ capsulitis without any noticing complications. KCI Citation Count: 2